A review of maternal behaviour in dogs and potential areas for further research. (6th December 2019) - Santos, N. R.; Beck, A.; Fontbonne, A.
Abstract : Here we review information on maternal behaviour in dogs, defined as a combination of all the acts of the mother towards her offspring, which begins before parturition and continues until weaning. In dogs, maternal care is measured using the most commonly observed behaviours, such as the time spent in contact, licking/grooming and nursing of the puppies. Since newborn puppies have a very limited capacity for movement, maternal interaction is essential to their survival, nourishment and protection. It is also an important element of the bonding process between puppies and the bitch and is thought to play a role in the social development of the puppies. Nevertheless, some questions still need to be clarified, such as the best way to quantify factors that may interfere with maternal behaviour. In recent studies, maternal care, or maternal style, was measured using a scoring system and found to be influenced by factors such as litter size, breed and parity, or even human interaction. However, the impact of the emotional state of the bitch and the quality of maternal behaviour on puppy survival and development remain unclear. The long‐lasting effects of mother–puppy interactions on puppy behaviour during their adult life are still poorly understood, despite their importance for breeders who wish to prevent future problem behaviours.